Worldwide impact of disease attributable to low physical activity for diabetes and kidney diseases - Ding, Ping; Qi, Lingyan; Wang, Jinglei; Tang, Min; Weng, Yujie (Frontiers in Endocrinology, 2025)
BackgroundWe aimed to examine patterns of diabetes and kidney disease due to Low physical activity (LPA) in 204 countries between 1990 and 2021.MethodsData were from the Global Burden of Disease (GBD) 2021. Age-standardized death rate (ASDR) and age standardized disability-adjusted life years (DALYs) were estimated. In addition, annual percentage changes (EAPC) were calculated.ResultsThe age-standardized DALY rate (EAPC = 0.89; 95% CI: 0.85, 0.93) and age-standardized death rate (ASDR) of diabetes and kidney disease due to LPA increased (EAPC = 0.34; 95% CI: 0.28,0.39) during 1990 to 2021. Among them, the age-standardized DALY rate and ASDR increased fastest in Eastern Europe (EAPC 2.43 and 3.79, respectively). Mauritius had the most significant increase in age-standardized DALY (EAPC = 3.40), while the Russian Federation had the most significant increase in ASDR (EAPC = 4.40). In 2021, both ASDR and age-standardized DALY rates per 100,000 people increased in women compared with men. The age-standardized DALY rate per 100,000 people generally showed an upward trend, with the highest in Oceania (285.33) and the highest ASDR in Southern Sub-Saharan Africa (10.56).ConclusionsThe global ASDR and age-standardized DALY rates reveal a significant surge in diabetes and kidney disease attributable to LPA from 1990 to 2021. This escalation is evident across 21 regions, with notable increases observed in Eastern Europe, Sub-Saharan Africa, and Oceania.